Strategi Peningkatan Kapasitas Penyuluh Pertanian dalam Penggunaan Cyber Extension di Kabupaten Tabanan (Jurnal Agribisnis dan Agrowisata, 2025)
Strategy for Increasing the Capacity of Agricultural Extension Workers in the Use of Cyber Extensions in Tabanan Regency. This study aims to analyze internal and external factors, develop alternative strategies, and priority alternative strategies in increase the capacity of agricultural extension workers in the use of Cyber Extension in Tabanan Regency. To achieve these goal, this study uses qualitative data and quantitative data with primary and secondary data sources. Data obtained through the process of interviews and documentation. Data that has been obtained then get analyzed using SWOT analysis and QSPM analysis. The results of research show the position of Cyber Extension in the position matrix is in quadrant I where Cyber Extension can use the Strength and Opportunity strategy, that is extension workers can use technology to introduce Cyber Extension to the farmers. The study of SWOT analysis resulted four alternative strategies, namely: (a) Strengths-Opportunities Strategy (utilizing technology in introducing Cyber Extension and improving the quality of writing), (b) Weaknesses-Opportunities Strategy (add the number of post verifiers, managing the agendas for writing), (c) Strengths-Threads Strategy (appliying the inovations, writing training to improve the skills of extension worker), (d) Weaknesses-Threads Strategy (reviewing informations in Cyber Extension, maintain writing continuity).
Keywords: Strategy; Cyber Extension; SWOT